Kepatuhan Pengelolaan Penyakit Diabetes mellitus Tipe II melalui Peer Group Support di Wilayah Kerja Puskesmas Kebonsari Surabaya - Yuyun Diatiningsih; Kusnanto Kusnanto; Abu Bakar (Universitas Airlangga, 2019)
Introduction: Diabetes Mellitus is a chronic disease that cannot be cured so that compliance is required to manage the disease. Patient compliance is in accordance with the provisions of the behavior of health workers. The aimed of this study was to analyze the effect of peer group support on the compliance of type 2 Diabetes mellitus disease management.Methods: This research was used a quasy experiment pre post test designed. The selection of sample using a purposive sampling and was obtained 16 respondents from 77 population. The independent variable was a peer group support that carried out for two weeks while dependent variable was dietary compliance, exercise and drugs consumption which data was collected by observation sheet. The data were analyzed using Wilcoxon Signed Rank Test and Mann Whitney U Test with significantvalue of ≤α 0.05.Result: The results showed that there was increase of dietary compliance (p=0.012) but there was no effect of peer group support for dietary compliance (p=0.14), the increase of exercise compliance (p=0.012) and there was effect of peer group support for exercisecompliance (p=0.004), and the increase of drugs consumption compliance (p=0.027) and there was effect of peer group support for drugs consumption compliance (p=0.048).Discussion: It can be concluded that peer group support had good effect to improve dietary compliance, exercise, and drugs consumption so that blood sugar could be controlled. Larger respondents, more proper instruments and longer duration of study will be needed to get a better result of the further research.